The Evolution of Sharia Fintech Contracts: A Systematic Review of Islamic Banking Ecosystem Integration in Indonesia (2020–2025) - Lailatul Mubarokah; Imamul Muttaqin; Ach. Bakir (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2026)
The acceleration of financial digitalization in Indonesia has positioned Islamic fintech as a crucial pillar within the banking ecosystem through linkage and channeling models. This study aims to map literature characteristics, analyze growth trends, dissect thematic contract transformations, and formulate strengthening strategies for Indonesia’s Islamic fintech-banking landscape. Utilizing a Systematic Literature Review (SLR) with the PRISMA protocol, 20 core articles were meticulously curated from 420 references spanning 2020–2025. Findings indicate a dominance of qualitative methods (60%), with an exponential surge in publications during 2024–2025 driven by post-pandemic regulatory shifts. Thematic synthesis reveals a significant transition from simple Murabahah contracts toward complex schemes such as Salam, Musyarakah, and Hybrid Contracts (al-uqud al-murakkabah). Nevertheless, a critical regulatory gap persists between DSN-MUI Fatwa No. 117/2018 and technical policies regarding digital risk mitigation. This study recommends harmonizing Lex Specialis laws, implementing Regulatory Technology (RegTech) for automated smart contract-based sharia audits, and optimizing the synergy of Islamic social funds (Ziswaf). These strategies aim to achieve financial inclusion aligned with Maqashid Sharia principles. Ultimately, the developed framework serves as a strategic blueprint for Muslim-majority countries to accelerate sharia-compliant digital financial integration globally.